2014
DOI: 10.3109/09273948.2013.874445
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Noninfectious Uveitis Treated with or without Systemic Anti-inflammatory Therapy

Abstract: Systemic therapy can be effectively used to control serious cases of noninfectious uveitis without significant relative adverse impact on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
12

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
0
10
0
12
Order By: Relevance
“…Non-infectious uveitis (NIU) is an umbrella term for a family of intraocular inflammatory conditions that collectively affect more than one in 1,000 individuals and account for ~10% of preventable blindness in Western countries ( 1 , 2 ). This typically recurrent or chronic disorder may lead to poor visual outcome and low quality of life if undertreated ( 3 , 4 ). Although corticosteroids (either local or systemically) remain the therapy of first choice, long term use is hampered by many side effects ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-infectious uveitis (NIU) is an umbrella term for a family of intraocular inflammatory conditions that collectively affect more than one in 1,000 individuals and account for ~10% of preventable blindness in Western countries ( 1 , 2 ). This typically recurrent or chronic disorder may lead to poor visual outcome and low quality of life if undertreated ( 3 , 4 ). Although corticosteroids (either local or systemically) remain the therapy of first choice, long term use is hampered by many side effects ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…21 Several studies have focused on the effect of uveitis symptoms on quality-of-life outcomes. [22][23][24][25][26][27] Given that both uveitis and corticosteroid therapy are related to an increased likelihood of complications, it may be difficult to determine disease vs treatment effect on comorbidity and quality of life. Moreover, noninfectious uveitis is associated with a number of systemic disorders, including Behçet disease, juvenile idiopathic arthritis, rheumatoid arthritis, Vogt-Koyanagi-Harada disease, sarcoidosis, ankylosing spondylitis, psoriatic arthritis, and multiple sclerosis.…”
mentioning
confidence: 99%
“…Medications include frequent eye drops (mydriatics and intraocular steroids), ocular injections, and systemic immunosuppressive therapy administered by injections or infusions. Interestingly, although these can potentially affect quality of life and function, a study in adults with uveitis demonstrated that those on systemic therapy had similar vision related and health related quality of life as those not on systemic therapy 5 . However, the effects of medication for uveitis in children are virtually unknown.…”
Section: Vision Related Quality Of Life and Functionmentioning
confidence: 99%